2003
DOI: 10.1364/ao.42.005765
|View full text |Cite
|
Sign up to set email alerts
|

Optical forces for noninvasive cellular analysis

Abstract: A novel, noninvasive measurement technique for quantitative cellular analysis is presented that utilizes the forces generated by an optical beam to evaluate the physical properties of live cells in suspension. In this analysis, a focused, near-infrared laser line with a high cross-sectional intensity gradient is rapidly scanned across a field of cells, and the interaction of those cells with the beam is monitored. The response of each cell to the laser depends on its size, structure, morphology, composition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Iron pentacarbonyl (Fe(CO) 5 ) (Kanto, 95%) and cobalt tricarbonyl nitrosyl (Co(CO) 3 NO) (Gelest, 95%) were degassed by freeze-pump-thaw cycles in the dark and purified by vacuum distillation immediately before use. To prepare a gaseous mixture, each vapor was introduced successively into a cross-shaped Pyrex cell having long (length 155 mm, inner diameter 35 mm) and short (length 80 mm, inner diameter 20 mm) arms or into a small cylindrical Pyrex cell (length 160 mm, inner diameter 20 mm, volume 50 cm 3 ) equipped with a couple of quartz windows through a vacuum line equipped with a capacitance manometer (Edwards Barocel Type 600). The background pressure of the irradiation cell was less than 8 × 10 −5 Torr (1 Torr = 133.3 Pa).…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron pentacarbonyl (Fe(CO) 5 ) (Kanto, 95%) and cobalt tricarbonyl nitrosyl (Co(CO) 3 NO) (Gelest, 95%) were degassed by freeze-pump-thaw cycles in the dark and purified by vacuum distillation immediately before use. To prepare a gaseous mixture, each vapor was introduced successively into a cross-shaped Pyrex cell having long (length 155 mm, inner diameter 35 mm) and short (length 80 mm, inner diameter 20 mm) arms or into a small cylindrical Pyrex cell (length 160 mm, inner diameter 20 mm, volume 50 cm 3 ) equipped with a couple of quartz windows through a vacuum line equipped with a capacitance manometer (Edwards Barocel Type 600). The background pressure of the irradiation cell was less than 8 × 10 −5 Torr (1 Torr = 133.3 Pa).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Therefore, the separation and analysis of a single microparticle is necessary to elucidate the function of microparticles in real systems. To perform them, nondestructive and noninvasive measurement techniques for the properties of an 'individual' single microparticle are extensively required in different research fields, such as biology, environmental chemistry, and medical science [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…This is the reason why a lot of techniques to investigate a single microparticle have been developed. [2][3][4][5][6][7] The migration analyses 8 can satisfy this requirement, since the microparticle can be caused to migrate by an extremely weak driving force. For example, only 10 -14 N is enough to move a particle of 1 μm radius at the velocity of 1 μm s -1 , which can be observed by a conventional optical microscope.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Dharmadhikari et al and Mohanty et al have shown that opticalinduced rotation of erythrocytes can be used for the early detection of malaria [16,17]. The classification of HeLa cells [18], viruses [3], and yeast cells [19] has also been demonstrated. Martin et al [12] have shown the discrimination of different breast cancer cells by measuring the optical deformabiliy.…”
Section: Introductionmentioning
confidence: 99%